2016
DOI: 10.5120/cae2016652272
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Multicrystalline Photovoltaic Module in Critical Climatic Conditions of Western Rajasthan, India

Abstract: The energy yield of a Photovoltaic (PV) power plant depends upon the dc power output of the PV module. The irradiance and temperature are the two most important parameters affecting the dc power output. This paper analyses the dc power output of a multicrystalline PV module in the realistic environmental condition with respect to solar irradiance, ambient temperature and cell temperature. The real time data is collected from a 5 MW grid connected solar PV plant located in Jaisalmer, a district in Western Rajas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In summers when the temperature is very high V dc is also high and nearly constant for about 8 hours irrespective of irradiance showing that at high cell temperature V dc becomes independent of irradiance, the most significant positive effect of high cell temperature. In the time duration when V dc is constant the P dc curve follows POA curve and correspondingly I dc curve as shown vide figure [16][17][18][19]. The dc current varies in direct proportion to irradiance and is verified by figures 20-23.…”
Section: Variation Of V Dc Poa Cell Temperature I Dc and P Dc Witmentioning
confidence: 72%
See 1 more Smart Citation
“…In summers when the temperature is very high V dc is also high and nearly constant for about 8 hours irrespective of irradiance showing that at high cell temperature V dc becomes independent of irradiance, the most significant positive effect of high cell temperature. In the time duration when V dc is constant the P dc curve follows POA curve and correspondingly I dc curve as shown vide figure [16][17][18][19]. The dc current varies in direct proportion to irradiance and is verified by figures 20-23.…”
Section: Variation Of V Dc Poa Cell Temperature I Dc and P Dc Witmentioning
confidence: 72%
“…Attari et al showed production in summer was more compared to winters for sites located in north of Morocco [13]. Few researchers showed that irradiance outweighs the negative effect of temperature leading to much higher energy yield in summers as compared to winters [14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Vasisht et al [4] have shown that ambient temperature between 20 to 38 o C has positive correlation with the efficiency of a monocrystalline PV system. The results of Garg et al [5] also show that dc voltage decreases with increase in temperature only for ambient temperature greater than 38 o C and cell temperature greater than 50 o C. Garg et al [6] have shown that dc power output varies in direct proportion to irradiance outweighing the change in temperature. Power output at cell temperature 50-55 o C was far greater than power output at 40 o C. Garg and JB [7] have also shown that dc voltage attains a point of saturation maintaining nearly constant value in the range of 80-85% of its rated value for cell temperature greater than 49 o C. Mustapha et al [8] while evaluating the performance of a polycrystalline solar photovoltaic module under Maiduguri-Nigeria weather conditions have shown that current generated is directly proportional to solar irradiance and is almost independent of temperature.…”
Section: Introductionmentioning
confidence: 99%
“…This paper illustrates comprehensive study of real field data to analyse the effect of high cell temperature and POA on the dc voltage of a grid connected multicrystalline module and to estimate temperature coefficient for multicrystalline module in real field conditions which is far different from laboratory conditions. The work done is extension of my previous two papers [4,5]. In previous paper [4] dc voltage was analysed with respect to ambient temperature and GHI (Global Horizontal Irradiance) but results show that V dc has better correlation with cell temperature and POA.…”
mentioning
confidence: 97%